Pengembangan Produk Choice Coffee Rempah Coffee Melalui Social Media Marketing - Agil Prasetyo Haryono (Bandung Conference Series: Business and Management, 2024)
Abstract. The Food and Beverage business, there is a business with processed coffee drinks, namely Choice Cinnamon White Coffee which has differences from other products, namely using cinnamon spices which makes Choice Cinnamon White Coffee products have benefits for the health of the body. Choice Cinnamon White Coffee in its business activities experiences problems, namely in business capital, management aspects such as production, marketing, finance and law so it is necessary to develop the business needed to overcome these problems. In managing the Choice Cinnamon White Coffee business, developing it through the use of social media as marketing Branding Activation. Researchers also use various strategies such as Business Model Canvas, SWOT analysis, Porter's Five Forces, Balanced Scorecard, Target and Performance, and BCG Matrix to carry out business development. The data collection techniques used are interviews, observation, and documentation. Interviews were conducted with consumers and direct competitors, while observations and documentation were conducted at Choice Cinnamon White Coffee business. The results of the research show that in developing Choice Cinnamon White Coffee business, it is necessary to seek more capital to cover a wider market and maximize activities in branding, preparation of financial reports, registration of legality such as halal products and various parties concerned with running business activities. Abstrak. Dalam usaha F&B (Food and Beverage), terdapat usaha dengan minuman olahan kopi yaitu Kopi Susu Rempah Choice yang memiliki perbedaan dengan produk lainnya, yaitu menggunakan rempah kayu manis yang menjadikan produk Kopi Susu Rempah Choice memiliki manfaat bagi kesehatan tubuh. Kopi Susu Rempah Choice dalam kegiatan usahanya mengalami permasalahan yaitu dalam modal usaha, aspek manajemen seperti produksi, pemasaran, keuangan dan hukum dengan begitu perlu pengembangan usaha yang diperlukan dalam mengatasi permasalahan tersebut. Dalam mengelola usaha Kopi Susu Rempah Choice, melakukan pengembangan melalui penggunaan media sosial sebagai pemasarannya dan menggunakan Branding Activation. Peneliti juga menggunakan berbagai strategi seperti Business Model Canvas, analisis SWOT, Five Forces Porter, Balanced Scorecard, Target and Performance, dan BCG Matrix untuk melakukan pengembangan usaha. Adapun teknik pengumpulan data yang digunakan yaitu wawancara, observasi, dan dokumentasi. Wawancara dilakukan kepada konsumen dan pesaing langsung, sedangkan observasi dan dokumentasi dilakukan pada usaha Kopi Susu Rempah Choice. Hasil dari penelitian menunjukan bahwa dalam pengembangan usaha Kopi Susu Rempah Choice, perlu mencari modal yang lebih untuk mencakup pasar lebih luas serta memaksimalkan kegiatan dalam branding, pembuatan laporan keuangan, pendaftaran legalitas seperti halal produk dan berbagai pihak yang bersangkutan dengan kegiatan usaha dijalankan